2018
DOI: 10.1007/s10803-018-3515-z
|View full text |Cite
|
Sign up to set email alerts
|

Processing Speed is Impaired in Adults with Autism Spectrum Disorder, and Relates to Social Communication Abilities

Abstract: Autism spectrum disorder (ASD) is characterized by a variety of social and non-social behavioral deficits. One potential mechanism that could unify this diverse profile of behaviors is slower processing speed. Seventy-six high-functioning adults with ASD were compared to 64 matched controls on standardized measures of processing speed. Participants with ASD were significantly slower on all measures, and on the composite score from the three tests (d's > .65). ASD participants with slower processing speeds scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 47 publications
2
44
1
Order By: Relevance
“…It may be that by using a deliberative decision-making style, autistic adolescents are able to fulfil their need to pay attention to detail, which in turn makes them feel satisfied and happier. We note that this may be seen to contradict previous studies (Haigh, Walsh, Mazefsky, Minshew, & Eack, 2018;Hedvall et al, 2013), which showed that slower processing speed in general was associated with negative outcomes. However those studies often relied on 'objectively measured' outcomes which may not reflect the views of autistic people about themselves.…”
Section: Discussioncontrasting
confidence: 98%
“…It may be that by using a deliberative decision-making style, autistic adolescents are able to fulfil their need to pay attention to detail, which in turn makes them feel satisfied and happier. We note that this may be seen to contradict previous studies (Haigh, Walsh, Mazefsky, Minshew, & Eack, 2018;Hedvall et al, 2013), which showed that slower processing speed in general was associated with negative outcomes. However those studies often relied on 'objectively measured' outcomes which may not reflect the views of autistic people about themselves.…”
Section: Discussioncontrasting
confidence: 98%
“…This pattern was also observed by Lever and colleagues (121), who similarly demonstrated that despite being as accurate as controls on an n-back task, adults with ASD took significantly longer to respond. Slower RTs may be indicative of slower processing speed, which has also been reported in ASD ( (122)(123)(124)(125)(126)(127); but see (128,129)). Whilst it may not affect performance on simple experimental STM or WM tasks, this trend towards longer responses or processing could have more noticeable effects in complex, everyday behaviours.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, it has been also shown that there exists a negative correlation between processing speed and sustained connectivity [King & Anderson, 2018]. Processing speed is one aspect of cognition that is impaired in ASD compared with typical development [Haigh, Walsh, Mazefsky, Minshew, & Eack, 2018;Travers et al, 2014]. Interestingly, Watanabe and Rees studied brain network dynamics using an energy-landscape analysis, and reported that highfunctioning adults with ASD show fewer neural transitions due to an unstable intermediate state [Watanabe & Rees, 2017].…”
Section: Discussionmentioning
confidence: 99%